Specifications-Based Grading in an Introduction to Proofs Course. Issue 2 (7th February 2018) - Williams, Kristopher
Abstract: This article describes a system of specifications-based grading used in an introduction to proofs course. The system was introduced to address two issues that arose in the course: how to spend less time grading and how to encourage use of feedback. We describe the implementation of the system and the results on grading and on students.